2019
DOI: 10.1104/pp.19.00034
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid Permease 5 (OsAAP5) Regulates Tiller Number and Grain Yield in Rice

Abstract: As fundamental nutrients, amino acids are important for rice (Oryza sativa) growth and development. Here, we identified the amino acid permease 5 (OsAAP5), that regulates tiller number and grain yield in rice. The OsAAP5 promoter sequence differed between indica and japonica rice varieties. Lower expression of OsAAP5 in the young leaf blade in indica varieties than in japonica varieties was associated with more tillers in indica than in japonica. Down-regulation of OsAAP5 expression in japonica using RNA inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 65 publications
(82 reference statements)
2
106
0
Order By: Relevance
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNAseq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Previous studies have elucidated the regulatory mechanisms of the axillary bud growth of plants grown under N stress [22,26,27,29,35,56]; however, many regulators and their regulatory mechanisms are still unclear. This work revealed that the growth rate of axillary buds was distinct in plants grown under different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under six different N concentrations via RNA-sEq.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid permeases (AAPs) are responsible for amino acid transport, of which there are 19 members in rice [33]. Studies of OsAPP3 [34], OsAPP5 [35], and OsNADH-GOGAT1 [36] indicated that external N status has a profound influence on axillary bud outgrowth and tiller number in rice. A previous study revealed that the growth and yield of plants increase when nitrate and ammonium are supplied simultaneously [37], but the gene regulatory networks and signalling pathways involved in axillary bud formation and outgrowth in response to different external N supplies are still poorly understood, especially the link between N and hormones with respect to axillary bud outgrowth.…”
mentioning
confidence: 99%